2011
DOI: 10.1155/2011/215653
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing DCDC5 in the Flanking Region of an LD‐SNP Derived from a Kidney‐Yang Deficiency Syndrome Family

Abstract: Objective. To explore the genetic traits of Kidney-yang deficiency syndrome (KDS). Design. Twelve KDS subjects and three spouses from a typical KDS family were recruited. Their genomic DNA samples were genotyped by Affymetrix 100K single-nucleotide polymorphism (SNP) arrays. The linkage disequilibrium (LD) SNPs were generated using GeneChip DNA analysis software (GDAS, Affymetrix). Genes located within 100 bp of the flanks of LD SNPs were mined via GeneView. 29 exons of the doublecortin domain containing 5 (DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Lu et al 27 studied a family with Yang-deficient constitution and found that all of the children and 10 out of 14 grandchildren (71.4%) of two Yang-deficient individuals were also Yang-deficient. Zhou et al 28 showed further evidence for the genetic basis of this constitution by finding genomic variations in DCDC5 associated with Yang-deficiency through linkage disequilibrium single nucleotide polymorphism gene sequencing on 12 family members and three spouses with Yang-deficiency syndrome. A genome-wide association study on Yang-deficient constitution by Yao et al 29 showed that Yang-deficient constitution had polygenic genetic characteristics, and found that polymorphism of RGS6, mGluR5, GAPDHL19 and IKZF1 genes were related to changes in cyclic AMP and cyclic guanosine monophosphate levels, memory, metabolic energy state and immune function respectively in Yang-deficient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al 27 studied a family with Yang-deficient constitution and found that all of the children and 10 out of 14 grandchildren (71.4%) of two Yang-deficient individuals were also Yang-deficient. Zhou et al 28 showed further evidence for the genetic basis of this constitution by finding genomic variations in DCDC5 associated with Yang-deficiency through linkage disequilibrium single nucleotide polymorphism gene sequencing on 12 family members and three spouses with Yang-deficiency syndrome. A genome-wide association study on Yang-deficient constitution by Yao et al 29 showed that Yang-deficient constitution had polygenic genetic characteristics, and found that polymorphism of RGS6, mGluR5, GAPDHL19 and IKZF1 genes were related to changes in cyclic AMP and cyclic guanosine monophosphate levels, memory, metabolic energy state and immune function respectively in Yang-deficient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhou et al and Ding et al have detected the linkage disequilibrium (LD) SNPs to explore the genetic traits of kidney-Yang deficiency ZHENG and found that kidney-Yang deficiency ZHENG is involved in special LD SNPs in the intragenic level and proved doublecortin domain containing 5 and other genes surrounding these SNPs display some relationships with key symptoms of kidney-Yang deficiency ZHENG [77, 78]. …”
Section: Applications Of Omics Technologies On Clinical Research Omentioning
confidence: 99%